2016
DOI: 10.4103/0366-6999.194635
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Application WeChat for Clinical Follow-up of Discharged Patients with Head and Neck Tumors

Abstract: Background:Nowadays, social media tools such as short message service, Twitter, video, and web-based systems are more and more used in clinical follow-up, making clinical follow-up much more time- and cost-effective than ever before. However, as the most popular social media in China, little is known about the utility of smartphone WeChat application in follow-up. In this study, we aimed to investigate the feasibility and superiority of WeChat application in clinical follow-up.Methods:A total of 108 patients d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 30 publications
4
73
0
Order By: Relevance
“…Telephone follow-up has been examined in both adult and paediatric populations following anorectal surgery, cholecystectomy, hernia repair, tonsillectomy and following endoscopy1 6–9 12 and has been found to be a safe and acceptable alternative with satisfaction rates exceeding 90% 1 2. In this digital age, other and better technologies can be employed to enhance contact between patient and hospital such as text messaging,23 interactive voice response systems24 25 or web-based assessment tools26 or smartphone applications 27. We are now using the results of this study as the basis for a proposal to compare/ascertain the feasibility and safety of a text message follow-up and compare it to a telephone follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Telephone follow-up has been examined in both adult and paediatric populations following anorectal surgery, cholecystectomy, hernia repair, tonsillectomy and following endoscopy1 6–9 12 and has been found to be a safe and acceptable alternative with satisfaction rates exceeding 90% 1 2. In this digital age, other and better technologies can be employed to enhance contact between patient and hospital such as text messaging,23 interactive voice response systems24 25 or web-based assessment tools26 or smartphone applications 27. We are now using the results of this study as the basis for a proposal to compare/ascertain the feasibility and safety of a text message follow-up and compare it to a telephone follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many patients do not receive reimbursement for PICC-related maintenance expenses, which can lead them to believe that delaying maintenance can save them money. In this context, Lyu et al [55] followed 108 patients with head and neck cancers for 6 months and found that WeChat follow-up was associated with better values for time consumption, economic cost, loss-to-follow-up rate, and patient satisfaction (vs. telephone follow-up). Other studies [19, 23] have also demonstrated that WeChat follow-up improves catheter maintenance dependence relative to telephone follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients require a professional and reliable platform to ensure that they receive accurate information, and WeChat follow-up platforms in China help address these issues by providing patients with access to professional teams and knowledge, regularly updated information, picture- and video-based explanations, and positive interactions with healthcare professionals. Moreover, Lyu et al [55] reported that WeChat interventions were more likely to create a friendly relationship between the patient and nurse (vs. telephone interventions), which makes the patient more likely to trust and follow the nurse’s guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigated the utility and impact of Wechat service in clinical follow-up (Feng et al, 2017;Lyu et al, 2016), and some aimed to determine the effectiveness of using MMA (WhatsApp and WeChat) as a clinical intervention (Iribarren et al, 2017;Johnston et al, 2015;W. Some investigated the utility and impact of Wechat service in clinical follow-up (Feng et al, 2017;Lyu et al, 2016), and some aimed to determine the effectiveness of using MMA (WhatsApp and WeChat) as a clinical intervention (Iribarren et al, 2017;Johnston et al, 2015;W.…”
mentioning
confidence: 99%
“…Previous studies have assessed application of MMA in health care, especially in clinical area. Some investigated the utility and impact of Wechat service in clinical follow-up (Feng et al, 2017;Lyu et al, 2016), and some aimed to determine the effectiveness of using MMA (WhatsApp and WeChat) as a clinical intervention (Iribarren et al, 2017;Johnston et al, 2015;W. Li, Han, Guo, & Sun, 2016) or an educational intervention for improving health literacy (X. .…”
mentioning
confidence: 99%